(untitled) (Revista Eletrônica: Tempo - Técnica - Território / Eletronic Magazine: Time - Technique - Territory, 2016)
Urban space is the one built by man , not the natural environment . The set of land uses that have joint organized and evenly , being set based on the interests of the promoters of urban space , which are the owners of the means of production, land owners, property developers , the state and excluded social groups, and this work has emphasized the role of property developers who work for the reproduction of capital and the state that also modifies the space of the city and often acts as a real estate developer financing ventures , acting in this way together with promoters estate .